Association between TMJ pathology and craniofacial morphology in patients with malocclusion - OHTANI, Jyunji; TANIMOTO, Kotaro; OZAWA, So; SANO, Ryota; KAMIYA, Takashi; SUGIYAMA, Hiroki; TANNE, Yuki; MITSUYOSHI, Tomomi; TANNE, Kazuo (Journal of the Japanese Society for the Temporomandibular Joint, 2010)
It has been suggested that there is a relationship between temporomandibular disorders (TMD) such as temporomandibular joint osteoarthritis (TMJ-OA) and craniofacial morphology. However, no definite conclusion has been reached due to the variety of TMJ pathology and natural course of TMD. The purpose of this study was to investigate the association between TMJ-OA and craniofacial morphology. Subjects were selected from orthodontic patients with signs and symptoms of TMD who underwent MRI examination before treatment from 1998 to 2008. The subjects were divided into three groups: patients with unilateral TMJ-OA (UOA group), patients with bilateral TMJ-OA (BOA group) and patients without TMJ-OA and disc displacement (N group). Craniofacial morphology was analyzed on postero-anterior and lateral cephalograms. Bonferroni correction was used for statistical comparisons among the three groups. As a result, the following measurement items showed significant differences between the BOA group and the other two groups (UOA group and N group), (∠ANB (p< 0.01), ∠SNB (p< 0.01), SN/MP (p< 0.01), PP/MP (p< 0.05) and Ar-Go (p< 0.01)). In the UOA group, all the patients exhibited mandibular lateral shift of the Me point to the symptomatic side. Moreover, the amount of lateral shift was significantly greater in the UOA group than in the other two groups (BOA and N groups). These findings showed that bilateral TMJ-OA is related to steep mandibular plane, short ramus height, retro-positioned mandible and the resultant skeletal II maxillo-mandibular relation. Unilateral TMJ-OA may be related to lateral shift of the mandible. It is thus suggested that there might be an association between the presence of TMJ-OA and craniofacial morphology in orthodontic patients.